Pengaruh Modal Usaha, Tenaga Kerja Dan Jam Kerja Terhadap Kinerja Usaha UMK Toko Kelontong Di Kecamatan Tambaksari Kota Surabaya - Hutomo, Achmad Adhiaksa; Mulyati, Awin; Pratiwi, Ni Made Ida (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study was to determine and analyse the effect of business capital, labour, and working hours on the business performance of grocery store MSEs in Tambaksari District, Surabaya City. The research method used is quantitative method. Quantitative methods are used to collect and analyse the necessary data. The sample technique used is non probability sampling with purposive sampling technique totalling 70 respondents. Based on this research, the research instrument used a questionnaire that was distributed directly. The questionnaire contains statements about the indicators in the variables of business capital, labour, working hours and business performance. The data obtained were then analysed using multiple linear regression methods to determine the effect between the independent variable and the dependent variable. The results showed that partially business capital and labour have an influence on the business performance of MSEs of grocery stores in Ploso Village, Tambaksari Subdistrict, Surabaya City. While in partial testing, the working hour variable has no effect on the business performance of MSE grocery stores in Ploso Village, Tambaksari Subdistrict, Surabaya City. Business capital, labour, and working hours have a positive effect on the business performance of MSE grocery stores in Ploso Village, Tambaksari Subdistrict, Surabaya City after being tested together. This shows that together they can affect business performance.